Neutrophil recruitment and intracellular vesicle transport: A short overview. (6th May 2020) - Masgrau‐Alsina, Sergi; Sperandio, Markus; Rohwedder, Ina
Abstract: Recruitment of neutrophils from the intravascular compartment into injured tissue is an essential component of the inflammatory response. It involves intracellular trafficking of vesicles within neutrophils and endothelial cells, both containing numerous proteins that have to be distributed in a tightly controlled and precise spatiotemporal fashion during the recruitment process. Rab proteins, a family of small GTPases, together with their effectors, are the key players in guiding and regulating the intracellular vesicle trafficking machinery during neutrophil recruitment. This review will provide a short overview on this process and highlight new findings as well as current controversies in the field.